Case Report: Rehabilitation of a giant meniscus cyst with a mixed tear - Jing Ji; Yali Wang; Xitao Li; Yuling Wang (Frontiers in Rehabilitation Sciences)
Giant meniscus cysts combined with mixed tears are relatively uncommon in clinical practice. The primary objective of rehabilitation is to restore knee joint function and prevent cyst recurrence. In this article, we discuss a series of rehabilitation strategies implemented for a patient who experienced both a giant meniscus cyst and a mixed tear.